2018
DOI: 10.1093/femsec/fiy071
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in Pinus radiata responses to nitrogen source are related to changes in the root microbiome

Abstract: Variation in traits within a plant species contributes to differences in soil physicochemistry and rhizosphere microbial communities. However, how intraspecific variation in plant responses to nitrogen (N) shapes these communities remains unclear. We studied whether plant responses to organic and inorganic N forms vary among genotypes, and if these responses were associated with variation in root-associated communities. We investigated how the root microbiomes of two Pinus radiata D. Don genotypes were altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Our findings support those of a growing number of studies showing that plant genotype affects soil microbial community composition (e.g., Aira et al., 2010; Gallart et al., 2018; Schweitzer et al., 2008; Shenton et al., 2016). This relationship has previously been observed in the saltmarsh plant Spartina alterniflora , where bacterial rhizosphere communities differed between genotypes and growth form (Zogg et al., 2018), as well as among S. alterniflora plants from different populations grown in a common garden (Nie et al., 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings support those of a growing number of studies showing that plant genotype affects soil microbial community composition (e.g., Aira et al., 2010; Gallart et al., 2018; Schweitzer et al., 2008; Shenton et al., 2016). This relationship has previously been observed in the saltmarsh plant Spartina alterniflora , where bacterial rhizosphere communities differed between genotypes and growth form (Zogg et al., 2018), as well as among S. alterniflora plants from different populations grown in a common garden (Nie et al., 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to genetic diversity, the identity of genotypes or phenotypes within populations of primary producers has been shown to affect ecosystem functions associated with nutrient cycling (Raffard et al, 2019). Many studies have detected differences in soil microbial community composition among plant genotypes (e.g., Aira et al, 2010;Gallart et al, 2018;Schweitzer et al, 2008;Shenton et al, 2016). Purahong et al (2016) found effects of both genetic diversity and tree genotypic identity on soil enzyme activity in a subtropical forest, but the results were not consistent across all four tree species in the study.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Climate-driven geographical variation in soil microorganisms (5) can drive the composition of plant microbiota due to the predominance of horizontal transmission (83). Alternatively, environmental variation, both abiotic (46) and biotic (66), can indirectly shape plant microbiota through plant responses. Interactions among microbes can also have large effects on community composition, in which the presence of particular microbial groups or even single taxa alter the plant microbiome via both antagonistic and beneficial interactions (20,37,121,129,140).…”
Section: Distancementioning
confidence: 99%
“…It remains unclear whether differences in tree growth after 2.5-years of N fertilisation with different N source are due to genotype-specific strategies of biomass allocation and root plasticity. However, a parallel study utilising the same field trial and two of ten P. radiata genotypes and the organic and inorganic N treatments, found clear evidence that intraspecific variation in response to N form is associated with shifts in composition of the root microbiome (Gallart et al 2018b).…”
Section: Discussionmentioning
confidence: 99%